Social Network Decline: Health Care Workers' Experiences of Quarantine - Marzieh Pazokian; Hanieh Molaee (Mashhad University of Medical Sciences, 2020)
Background: Quarantine is one of the ways to control and prevent infectious diseases, such as Coronavirus Disease 2019 (COVID-19). Health care workers, who may have the experience of being quarantined, are among the people at risk for this disease. Aim: This study aimed to explore the health care workers' perspective of quarantine. Method: This qualitative study was conducted based on a descriptive design. The data were collected through semi-structured interviews with 18 health care workers infected with COVID-19. The participants were selected through purposive sampling, and the data were analyzed by a contractual qualitative content analysis based on Graneheim and Landman's approach. After an overview of each interview, semantic units, codes, as well as subcategories and categories were extracted through MAXQDA software (version 10) to obtain the themes. Results: The main theme obtained from this qualitative study was "support network decline" consisted of three categories, namely psychological concerns, job concerns, and self-imposed social isolation, accompanied by six subcategories. Implications for Practice: The support network can develop lifestyle as a factor for health care workers. Therefore, the promotion of support network will exert positive impact on social life of the health care workers.